CONDUCT DISORDER IN CROWDSTROIA’S NOVEL ARKAIS - Mahlina Sariani Harahap; M. Manugeren; Purwarno Purwarno (Universitas Islam Sumatera Utara (UISU), 2020)
This study aimed to find out and describe the sign of conduct disorder reflected in Crowdstroia’s novel Arkais. Conduct disorder (CD) is a mental disorder diagnosed in childhood or adolescence that presents itself through a repetitive and persistent pattern of behavior in which the basic rights of others or major age-appropriate norms are violated. A person diagnosed with conduct disorder can be cruel to both people and animals with the use of violence. The data analysis technique used is descriptive qualitative analysis. The descriptive research attempts to describe, explain and interpret conditions of the present or descriptive research seeks to provide an accurate description of observations of a phenomenon. The study is based on Psychological approach generally, and specifically on ‘Conduct Disorder’. The result showed the causes, the signs and and the traumatic of conduct disorder covering physical violence, aphatetic, and insecurity.